Stakeholders’ views on public-private partnerships for rehabilitation services in South Africa ahead of National Health Insurance - Senzelwe M. Mazibuko; Pragashnie Govender; Thayananthee Nadasan (South African Family Practice)
Background: Quality rehabilitation services are limited in rural South African areas, such as KwaZulu-Natal (KZN). Public-private partnerships (PPPs) are increasingly valued as an effective model for public health delivery in developing countries; yet, their application in South Africa’s rehabilitation sector, especially with the upcoming National Health Insurance (NHI) for universal health coverage, remains unclear. This study examined perspectives on using PPPs for rehabilitation services within the District Health System in KZN in preparation for the NHI.